Variação morfológica e sedimentar em praias da ilha de algodoal ( Litoral Amazônico ) - SOUSA, Lygia Nassar (2019)
The coastal zone is extremely dynamic and its morphology depends on climatic, geologic and physical factors. The Algodoal Island, which is focused in the present study, is located at the northeast of Pará State, being part of the Amazon coastal zone. With the aim to understand the local beach morphodynamics, two different beaches (Praia da Princesa e Praia da Caixa d’Água) were evaluated using topographic profiling and sediment sampling along a year, within the main climatic/hydrodynamic periods: december/08 (end of the dry season), march/09 (high rain season and equinoctial tides), may/09 (maximum fluvial discharge), september/09 (high dry season, strong winds and equinoctial tides) and december/09, enclosing the annual cycle. The results have shown a very dynamic area, but indicating a long-term stability. The results showed a general erosional tendency for both beaches. Between dez/08 and mar/09 the sediment balance was negative, being approx. -77 m³/m for Profile 1 (Praia da Princesa) and -48 m³/m for Profile 2 (Praia da Caixa d’Água). This erosion was attributed to the equinoctial tides, as well as water table flow at the beach face, improving erosion by backwash, affecting both beaches. From mar/09 to may/09 the sedimentary balance was positive for the two beaches: 15 m³/m for Praia da Princesa and 40 m³/m at the Praia da Caixa d’Água. In this case the deposition was correlated to the gradual reduction in tidal range after the equinoctial tides of march and the maximum fluvial discharge period of may, which also affects both beaches, especially at the Praia da Caixa d’Água, due to its location in the Marapanim estuary. Between may/09 and sep/09 the sedimentary balance was again negative in both beaches, although the erosion was much more conspicuously at the Praia da Caixa d’Água (-52 m³/m) than in the Praia da Princesa (- 11 m³/m). Considering the strong easterly winds of september, they result in erosion in the exposed Praia da Princesa region and aeolian transport toward the Praia da Caixa d’Água area. Furthermore, the equinoctial tides of september would also imply in erosion of both beaches. From sep/09 to dez/09 slight deposition was observed in both beaches (9 and 4 m³/m for Princesa and Caixa d’Água beaches, respectively). Comparing dez/08 and dez/09 one could observe strong erosion in both beaches: -63 m³/m (Praia da Princesa) and -55 m³/m (Praia da Caixa d’Água). This erosion seems to be the result of episodic migration of subtidal sediment banks. The observed variations in each profile place the Praia da Princesa as a dissipative oceanic beach, where the main morphological changes are the result of bar/trough migration. Furthermore, the Praia da Caixa d’Água is classified as an estuarine beach of the reflective with low tide terrace type. Therefore, waves are affecting especially the Princesa beach, whereas fluvial discharge is affecting especially the Caixa d’Água beach, as expected. During the dry season winds are resulting in erosion in Princesa beach 10 and deposition in Caixa d’Água beach, because of wind direction and beach orientation. The results on granulometric analyses corroborate to the interpretation of topographic changes, where grain size, asymmetry and sorting indicate erosion or deposition of aeolian sediments, as well as muddy sediments from the fluvial discharge. The results represent a good characterization of the evaluated profiles and beaches, and of the acting processes in oceanic and estuarine beaches of the Amazon littoral. Though it is helpful for further studies in any beach of the Amazon littoral, where rain/fluvial discharge seasonality, as well as macrotidal regime imply in a complex beach morphodynamics.